A simple cost effective screening test for microalbuminuria - Peiris, H.; Keerthi, A.A.P.; Hewage, U.C.L.; Fernando, D.J.S (My University, 2003)
Estimation of urinary albumin excretion in micro quantities requires expensive immunochemical methods which are not freely available in developing countries with limited resources. A study was performed to set up a simple cost-effective test to quantitatively assess the microalbuminwia. Urine specimens (l 73 samples) were collected and albumin concentration was estimated by precipitating with 25% sulphosalicylic acid (SSA) and use of a light dependent resistor (LDR) system. As the sensitivity of LDR system was interfered by the colour pigment of urine, all samples were mn through a Sephadex G-25 micro column to separate the colour pigment. The present test detects albumin concentrations in the range 10-200 mg/L with a sensitivity and specificity values of 83 andTgYorespectively. We conclude that the present LDR micro column gel filtration method can be used as a cost -qffective screening test for microalbuminuria in developing countries.